2020
DOI: 10.3390/app10249113
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian and Multi-Class Vehicle Classification in Radar Systems Using Rulex Software on the Raspberry Pi

Abstract: Nowadays, cities can be perceived as increasingly dangerous places. Usually, CCTV is one of the main technologies used in a modern security system. However, poor light situations or bad weather conditions (rain, fog, etc.) limit the detection capabilities of image-based systems. Microwave radar detection systems can be an answer to this limitation and take advantage of the results obtained by low-cost technologies for the automotive market. Transportation by car may be dangerous, and every year car accidents l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Namely, Car, Truck, and Motorcycle where the dataset contains 120 records. In [ 27 ], a multiclass tree-based classification technique was implemented to improve the prediction accuracy using this dataset.…”
Section: Forecast Resultsmentioning
confidence: 99%
“…Namely, Car, Truck, and Motorcycle where the dataset contains 120 records. In [ 27 ], a multiclass tree-based classification technique was implemented to improve the prediction accuracy using this dataset.…”
Section: Forecast Resultsmentioning
confidence: 99%
“…Lee et al [23] used CNN as an identifier using power-normalized Cepstral coefficients (PNCC) as a feature for the identification of underwater objects in the active sonar. Daher et al [24] identified various classes based on Rulex [25], a high-performance machine learning package, using 24 GHz radar data. Forecasts with a varying number of classes were performed with one, two, or three classes of vehicles and one for humans.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, instead of relying on multiple algorithms, the solution outputs the desired likelihood directly. Also focusing on optimizing the classification of moving objects, Ali Walid Daher et al [ 41 ] present a solution by applying machine learning. By using a Raspberry Pi for the training and testing purpose, IoT is introduced in their work.…”
Section: Previous Workmentioning
confidence: 99%